Intergasi Pendidikan Karakter Kerjasama dalam Pemainanan Tradisional - Vinsensia Kewa Lolong; Maximiliana Wua Lolong (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This study is motivated by the declining interest of children in traditional games due to the rapid development of digital technology. Traditional games, however, hold great potential as a medium for character education, particularly in fostering values of cooperation, responsibility, and social interaction. The purpose of this study is to analyze the character value of cooperation that emerges through the implementation of traditional games among students and to evaluate its effectiveness in enhancing social interaction within the school environment. The study employs a descriptive quantitative approach involving 23 students from SMPK Santo Don Bosco Lewoleba. Data were collected using a Likert-scale questionnaire comprising five indicators of cooperation: active participation, polite communication, care and support, acceptance of decisions, and responsibility and honesty. Data analysis was conducted by calculating the mean score for each indicator and converting it into qualitative categories. The findings reveal that the implementation of traditional games develops students’ cooperation values at a very good level, with an average score of 3.55. This indicates that traditional games contribute positively to students’ character formation, particularly in fostering teamwork, respect for peers, and harmonious social relationships. The study implies that traditional games can serve as an effective and enjoyable contextual learning medium to strengthen character education in primary and secondary schools.